An overview of experimental simulations of microbial activity in early Earth - Zhao, Mingyu; Zhao, Yao; Lin, Wei; Xiao, Ke-Qing (Frontiers in Microbiology, 2023)
Microbial activity has shaped the evolution of the ocean and atmosphere throughout the Earth history. Thus, experimental simulations of microbial metabolism under the environment conditions of the early Earth can provide vital information regarding biogeochemical cycles and the interaction and coevolution between life and environment, with important implications for extraterrestrial exploration. In this review, we discuss the current scope and knowledge of experimental simulations of microbial activity in environments representative of those of early Earth, with perspectives on future studies. Inclusive experimental simulations involving multiple species, and cultivation experiments with more constraints on environmental conditions similar to early Earth would significantly advance our understanding of the biogeochemical cycles of the geological past.